Outcomes of Operative and Non-operative Treatment of Adolescent Mid-diaphyseal Clavicle Fractures. Issue 7 (29th July 2014) - Heyworth, Benton E.; May, Collin; Carsen, Sasha; Donohue, Kyna; Miller, Patricia; Kramer, Dennis E.; Kocher, Mininder S.; Bae, Donald S.
Objectives: The optimal treatment approach to clavicle fractures in adolescents remains an area of significant controversy. The purpose of this study was to review the demographic characteristics, treatment approaches, and complications in a large series of adolescent clavicle fractures receiving operative and non-operative treatment. Methods: Radiographic and medical record review was conducted for all cases of patients ages 10-18 years-old who presented to a single tertiary care children's hospital between 2003-2012 with a mid-diaphyseal clavicle fracture. Demographic data, radiographic features, such as fracture pattern, operative details when applicable, and post-treatment clinical course was analyzed, including the reported time to healing and any known complications. Results: Out of 641 cases reviewed (79% male; mean age 14.3 years), 408 (64%) fractures were sustained during sports, most frequently football (25%), hockey (18%), soccer (12%), snowboarding (12%) and skiing (9%). Other common mechanisms of injury were falls sustained outside of athletic activity (19%) and motor vehicle accidents (5%), with similar distribution of mechanism and similar rates of associated injuries seen within the operative (5%) and non-operative (6%) treatment groups. Greater numbers of clavicle fractures were seen annually over the study period. Among the overall cohort, 82% were treated non-operatively, while 18% were treated surgically, with increasing percentage of patients undergoing surgery over the course of the study period. The mean age was higher in the operative group (15.5 years) than the nonoperative group (14.1 years)(p<0.001). Fifty-eight documented complications occurred in 46 patients (7.2%), were significantly more common in the operative (16%) group than the non-operative (5%) group (p<0.001), and were more common in older patients (p=0.007). Only 1 case of nonunion occurred in each treatment group (p=0.56). The rate of symptomatic implants was 13% in the operative group (leading to plate removal in 9% cases), while the rate of symptomatic malunion was 2% in the nonoperative group. Refracture was significantly more common in the nonoperative group (3%) than the operative group (2%) (p=0.03). Refracture in the non-operative group most commonly occurred in the period before complete healing had occurred. Of the 2 cases of refracture in the operative group, 1 case was a peri-implant fracture and 1 case occurred over 1 year following plate removal. No infections were reported in either group. One of the nonoperative symptomatic malunion patients developed thoracic outlet syndrome requiring osteotomy, which led to symptom resolution. One of the operative patients developed contralateral recurrent laryngeal and hypoglossal neuropraxia (Tapia's syndrome), causing vocal cord paralysis, tongue deviation, and hoarseness, with near complete resolution at the time of most recent follow up, four months post-operatively. Conclusion: Greater numbers of clavicle fractures are being seen in the adolescent population, with over 60% of cases occurring during sports and an increasing trend towards operative treatment in recent years. Nonunion and symptomatic malunion are rare in adolescents. While refracture is more common following nonoperative treatment, overall complication rates appear to be more common following operative management, the most common of which is symptomatic implants.